A numerical study of fluid–solid interaction in screw compressors. (10th May 2006) - Kovacevic, Ahmed; Stosic, Nikola; Smith, Ian K.
Efforts are continually being made to produce screw compressors with smaller clearances in order to reduce internal leakage. However, since the compression process induces large pressure differences across the rotors and temperature rise, they deform. A reliable method of estimating the interaction between fluid flow parameters and rotor deflection is thus needed in order to minimise clearances while avoiding contact between the rotors and the casing. A 3-D mathematical procedure is presented here to generate a numerical grid comprising both solid and fluid domains. This can be used to calculate the fluid flow and compressor structural deformation simultaneously by means of a suitable commercial numerical solver. Simulation results demonstrate the effects of change in working clearances, caused by rotor deformation, on compressor performance.